EFEK TERAPI BRONKODILATOR DAN KORTIKOSTEROID TERHADAP PERUBAHAN NILAI ARUS PUNCAK EKSPIRASI (APE) PASIEN PENYAKIT PARU OBSTRUKTIF KRONIK (PPOK) - Putu Rika Veryanti; I Dewa Gede Wisesa Budiman (FORTE JOURNAL, 2021)
Chronic obstructive pulmonary disease (COPD) is a disorder that occurs in the respiratory tract, which is characterized by narrowing, chronic obstruction of airway flow and causing shortness of breath. Bronchodilators and corticosteroids are the first-line therapy for COPD. Appropriate and effective therapeutic management can reduce COPD morbidity and mortality. However, we still found some problems related to the effectiveness of therapy in hospitalized COPD patients. One of the important parameters that need to be monitored in COPD patients is the peak expiratory flow. The purpose of this study was to determine the effect of the use of bronchodilators and corticosteroids on the peak expiratory flow value of COPD patients. This research was conducted at Persahabatan Hospital Jakarta with a cross-sectional study design. The sample that used in this study was patient medical records for the period 2018. The inclusion criteria were patient who diagnosed with COPD, received bronchodilator and corticosteroid therapy and had complete peak expiratory flow value. The number of samples is 99 and determined through purposive sampling. The data were analyzed statistically using paired t-test. The results of this study showed that bronchodilator and corticosteroid therapy could increase the peak expiratory flow value of COPD patients by (49.85±43.61) L/minute or (46.05±51.15) %. A total of 94.95% of patients experienced an increase in peak expiratory flow values ​​and 73.74% patients had an increase in peak expiratory flow ≥ 15%. Bronchodilator and corticosteroids had a significant effect on the peak expiratory current in COPD patients (p=0.000).